Сравнение двойного Z-инвертора с классическим инвертором для системы электроснабжения самолета - Хлебников, А.С.; Бачурин, П.А.; Гейст, А.В.; Решетников, А.Н.; Балагуров, М.В. (Технічна електродинаміка, 2012)
The scheme of the dual Z-Source inverter with the raised quality of formed voltages is proposed. Results of modeling of the converter as a part of aviation system of generating of electric energy are presented; comparison of this scheme with the scheme of the classical voltage source inverter is made.